CONSTITUTIONAL FOUNDATIONS OF THE EXECUTION OF THE ECtHR JUDGMENTS IN THE LEGAL SYSTEM OF THE RUSSIAN FEDERATION - K. Aranovskiy; S. Knyazev (Правоприменение, 2017)
The article studies binding legal force of the ECtHR decisions in relation to the arising from the Constitution of the Russian Federation and the Convention for the Protection of Human Rights and Fundamental Freedoms requirement demanding execution of measures of individual and general character. The authors analyze the legal positions of the Constitutional Court of the Russian Federation regarding the binding nature of ECtHR judgments. The authors note that, in assessing the nature of the decisions of this Court, their influence on the Russian legal system, it is important to take into account the fact that the legal effect of its decisions is not limited only to decrees adopted in the cases on the appeals against the Russian Federation. The article emphasizes, the Constitutional Court of the Russian Federation has never denied the role and importance of the ECtHR decisions in the Russian legal system, their commitment and the need of execution addressed to the Russian authorities of the individual measures, confidently and consistently perceiving the rights and freedoms of a person in the essential constitutional-Convention unity. The main difficulties of implementation or, as they say, domestication (domestication) of the Convention's provisions for Russia are connected not with the Convention itself and its interpretation in the decisions of the ECtHR. These difficulties are not sustainable and ambitious nature. Based on the anal-ysis of legal positions of the Constitutional Court of the Russian Federation and the ECtHR, the authors come to the conclusion that the Russian Federation shall make all possible efforts for the execution of final judgments of the Strasbourg Court which, however, does notrelieve Russian authorities from the unconditional compliance with the Constitution and which, in its turn, as a consequence, may hinder the execution of such judgments in case of their contradiction to the Constitution of Russia.